Phosphate ions as corrosion inhibitors for reinforcement steel in chloride-rich environment - Yohai del Cerro, Lucía (2013)
Phosphate ions were evaluated as corrosion inhibitors in solutions that simulate the composition of the pores in concrete contaminated with chloride ions. Cyclic voltammograms and potentiodynamic polarization tests were complemented with micro-Raman spectroscopy and impedance spectroscopy to follow the performance of this inhibitor. Long term performance involved weight loss evaluation. Chloride contamination increases the accumulation of corrosion products on the metallic surface and promotes pitting corrosion. In contrast, pitting is inhibited when phosphate ions are incorporated in a 1:1 phosphate to chloride molar ratio, even after a 90 days exposure. Micro Raman spectra clearly show the incorporation of phosphates to the passive film. Impedance spectroscopy results can be interpreted assuming a duplex surface film formed in the presence of phosphates. In the conditions of this investigation, phosphate ions behave as mixed-type corrosion inhibitors, protecting steel against corrosion in chloride-contaminated environments.